Should we use legitimate fallacies? A case study of whataboutism in the discourse on the Russian-Ukrainian war - Kiš, Serhij (My University, 2024)
Although the use of argumentative fallacies is generally prohibited in discourse, a significant part of fallacy studies consists in identifying the specific circumstances where the use of a fallacy is permissible. However, this literature often remains silent on whether a fallacy should be used even when deemed legitimate. This silence is problematic, as it suggests that the legitimacy is the sole criterion for deploying a fallacy. In this paper, I challenge this approach by demonstrating that even when a fallacy is legitimate, its use could still jeopardize the arguer’s goals. I base this argument on an analysis of a specific instance of the whataboutism fallacy used by Noam Chomsky in his commentary on the Russian invasion of Ukraine. I show that Chomsky’s references to the United States’ actions in Afghanistan and Iraq are better understood as broadening the context of the discussion rather than distracting or even justifying Russian actions. This is what makes Chomsky’s whataboutisms plausibly legitimate. But while these whataboutisms might be legitimate, I argue, drawing on a cost-benefit analysis of decision to argue framework, that Chomsky has compelling reasons to avoid using them. Real-life examples show that such arguments are prone to misunderstanding and misuse. I conclude that the risks associated with Chomsky’s whataboutism outweigh the potential benefits, suggesting that he should avoid their deployment. This case study reveals a broader lesson for the fallacy literature: it must explicitly address whether the legitimacy of a fallacy is sufficient justification for its use.
Měli bychom používat legitimní argumentační klamy? Případová studie apelu na pokrytectví v diskurzu o rusko-ukrajinské válce
Keywords: Cost-benefit analysis; decision to argue; fallacy; Noam Chomsky; Russian-Ukrainian war; whataboutism; analýza nákladů a zisků; argumentační klam; Noam Chomsky; rozhodnutí argumentovat; rusko-ukrajinská válka; whataboutismus